Assessing Agricultural Export Evidence on Economic Growth in Nigeria (1999-2020) - Okuduwor A. A; Amadi Robert C.C; Udi O.F (International Journal of Business and Applied Economics, 2023)
This study examined the impact of agriculture export on economic growth in Nigeria from 1999 to 2020. Specifically, the study investigated the impact of agriculture exports (as percentage of merchandize export), exchange rate and trade openness on economic growth (measured using gross domestic product growth rate). Annual data used for the study were sourced from World Development Indicator (WDI) and Central Bank of Nigeria (CBN) Statistical Bulletin. The study used econometric techniques of Augmented Dickey-Fuller (ADF), bound test and autoregressive distributed lag (ARDL) for empirical analysis. The results of unit root suggested that GDP growth rate and agriculture export were stationary while exchange rate and trade openness were non-stationary of order one. The findings from the autoregressive distributed lag (ARDL) method show that agriculture export contribute positive to economic growth. Exchange rate has a positive and significant impact on the Nigerian economy. Furthermore, the ARDL result show that trade openness has a positive and insignificant impact on economic growth. It was recommended that the Federal Government should formulate policies that will increase investment in the agriculture sector in order to optimize its positive contribution to the Nigerian economy.